Repeated two cycles of ulipristal acetate treatment improve the quality of life in premenopausal women with heavy menstrual bleeding dependent on uterine myomas, without impairment of bone health. (2nd September 2019) - Neri, Manuela; Pilloni, Monica; Paoletti, Anna Maria; Melis, Gian Benedetto; Piras, Bruno; Ajossa, Silvia; Marotto, Maria Francesca; Corda, Valentina; Ronchi, Alessandro; Giancane, Elena; Vallerino, Valerio; Saba, Alessandra; et al.
Abstract: This observational study was conducted in premenopausal women who presented themselves at the Obstetrics and Gynecology Department of the University Hospital of Cagliari (Italy), for heavy menstrual bleeding (HMB) dependent on uterine myomas. After a screening visit, 19 women without contraindications to ulipristal acetate (UPA) treatment, were included in the study that envisaged 12 months of observation in which each subject was asked to assume UPA (tablet of 5 mg, ESMYA ®, one tablet a day for 3 months: first cycle) two menstrual cycles of interruption and a second ESMYA ® cycle, followed by 3 months of observation (third follow-up month, visit 4). The significant decrease of myoma volume, diagnosed after the first ESMYA ® cycle, persisted until the visit 4. The HMB significantly decreased during the ESMYA ® treatment and persisted until visit 4. The quality of life (QoL), evaluated with the questionnaire SF-36, significantly improved during the study. The values of estradiol (E2), biochemical parameters of bone metabolism, as well as those of lumbar and hip bone mineral density, did not change during the study in comparison with basal levels. The efficacy of two repeated ESMYA ® cycles to treat uterine myomas and their related symptoms improves the QoL without interfering with bone health.